Relaksasi Pernafasan dengan Teknik Ballon Blowing terhadap Peningkatan Saturasi Oksigen pada Pasien PPOK - Ni Made Dwi Yunica Astriani; Putu Indah Sintya Dewi; Kadek Hendri Yanti (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to determine the effect of respiratory relaxation with the ballon blowing technique on increasing oxygen saturation in COPD patients. The study design used a one group pre-post test design. The results of the 30 COPD respondents showed the gender prevalence of the majority of male respondents 73.3% with an average age of 61.87 with an age range of 45-80 years, the mean (pre-test) was 89, 27 and the post-test mean is 94.53 with a p-value of 0,000. Conclusions, there Is An Influence of breathing relaxation with ballon blowing technique on increasing oxygen saturation in COPD patients in RSUD Buleleng Regency. Keywords: Increased Oxygen Saturation, COPD, Ballon Blowing Technique